2020
DOI: 10.1212/wnl.0000000000010347
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis–derived cognitive profile predicting early dementia conversion in PD

Abstract: Objectives:To investigate which baseline neuropsychological profile predicts the risk of developing dementia in early-stage Parkinson’s disease (PD).Methods:We retrospectively reviewed detailed medical records of 350 drug-naïve patients with early-stage PD (follow-up > 3 years), who underwent a detailed neuropsychological test at initial assessment. Factor analysis was conducted to determine cognitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 46 publications
2
67
1
Order By: Relevance
“…The CamPaIGN study found that posterior cortical defi cits were closely related to incident dementia in PD 41 . Meanwhile, other studies showed that frontal/executive dysfunction and frontal atrophy were associated with a higher risk for dementia conversion [42][43][44] . The discrep ancies might be ascribed to different genetic or eth nic backgrounds.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The CamPaIGN study found that posterior cortical defi cits were closely related to incident dementia in PD 41 . Meanwhile, other studies showed that frontal/executive dysfunction and frontal atrophy were associated with a higher risk for dementia conversion [42][43][44] . The discrep ancies might be ascribed to different genetic or eth nic backgrounds.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Interestingly, VN-FPN connectivity increased over 1 year in a mixed PDCN/PDMCI cohort, but not healthy controls ( Klobusiakova et al, 2019 ), and did not correlate with cognition. Our finding indicates this internetwork coupling topology is an early signature of high-level visual disturbances in PD ( Weil et al, 2016 ), which is of keen interest as early visuospatial decline is a risk for MCI and dementia ( Williams-Gray et al, 2013 ; Hong et al, 2014 ; Hobson and Meara, 2015 ; Garcia-Diaz et al, 2018 ; Chung et al, 2020 ; Ohdake et al, 2020 ).…”
Section: Discussionmentioning
confidence: 66%
“…Baseline neuropsychological profile in early-stage PD may predict the risk of developing dementia. Factor analysis in a previous study [ 22 ] demonstrated that the composite of executive, visuospatial and verbal memory deficits was associated with a higher risk of dementia conversion. Among them, frontal/executive dysfunction contributed most to the occurrence of PDD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factor analysis in a previous study [ 22 ] demonstrated that the composite of executive, visuospatial and verbal memory deficits was associated with a higher risk of dementia conversion. Among them, frontal/executive dysfunction contributed most to the occurrence of PDD [ 22 ]. The consistency with previous results allows us to confirm the value of MoCA-BC in assessing MCI in Chinese PD patients.…”
Section: Discussionmentioning
confidence: 99%